EARLY HEART DISORDERS IN HYPERTENSIVE PERSONS AS THE RESULTS OF PREVENTIVE EXAMINATION ON INDUSTRIAL ENTERPRISE - A. N. Britov; E. M. Platonova; T. V. Ryzova; N. A. Eliseeva (Кардиоваскулярная терапия и профилактика, 2014)
The article is considered on the questions of pathogenesis, clinic and diagnosis of myocardial disorders, first of all in persons with high blood pressure. Preference of ultrasound cardiography (UC) for detection of concentric and eccentric hypertrophy of left heart ventricle as well as concentric remodeling is shown. Authors claim the principle possibility to use UC methods in the plant out-patient department; it has principal significance for economically active persons. 2557 industrial workers 20–60 years (1492 men and 1065 women) were investigated. Hypertension (140/90 mm Hg or antihypertensive treatment) was diagnosed in 20% — 514 persons. Voltage ECG LVH criteria were found in 142 pts (28%); UC signs of LVH were found in 389 pts (76%). Increase of related thickness of heart walls diagnosed in 412 pts (80%) and increase of Mass myocardial index — in 347 pts (67%), diastolic dysfunction was found in 402 pts (78%). So the exclusive value of modern diagnostic methods including UC is proven which gives the possibility of early diagnostic of prevalent heart disorders in hypertensive industrial workers.